Tourism development in mining community - Kozhin, Semen (UiT The Arctic University of Norway, 2020)
The aim of this research project is to study the development of tourism in the mining community. As a case of study, the city of Kirovsk (Murmansk region, Russia) was chosen. Kirovsk have for the last 90 year been considered a monotown, much dependent upon mining as an economic practice. Presently tourism is being introduced and Kirovsk have been successful in relation to tourism investments. With the study of the Kirovsk case as an example of successful tourism development, the thesis draw attention to the future of tourism in the resource-extracting communities. The methods of research are based on quantitative and qualitative analysis of Instagram profiles of tourists who visited the destination to identify their preferences in the tourist market and their attention to mining and Arctic nature inside destination. Such research design makes it possible to identify what are the tourist activities that are preferred by tourist visiting a mining community, how and what do they rate of existing offers. In addition, the thesis engages with the question on if and how Kirovsk being a mining site disrupt the touristic experience and in the final arguments of the thesis I will discuss the opportunities for further development. A qualitative analysis of the narratives made through blog-post have been made. Based on previous studies, aspects of the relationship between mining and tourism within the resource-producing community have been identified. The study provides an understanding that tourism can become an important industry for building sustainability within northern resource-extracting community.